Robust design of high order repetitive controllers under control saturation. Issue 25 (2018) - Flores, Gabriel P.; Flores, Jeferson V.
Abstract: This paper presents a methodology to simultaneously design a high order repetitive controller (HORC) and an anti-windup compensator for systems subject to control saturation and parametric uncertainties. With the proposed structure it is possible to ensure a certain level of steady-state tracking and/or rejection performance when dealing with uncertain periodic signals. Based on a modified state-feedback formulation of the HORC and an static anti-windup structure, linear matrix inequality (LMI) conditions are proposed to guarantee closed-loop stability provided that the state trajectory and the reference/disturbance signals are inside admissible sets. A systematic procedure to determine upper bounds for the system initial conditions and maximum reference/disturbance values is also proposed. A numerical example illustrates the method.